2016
DOI: 10.4137/cmc.s39706
|View full text |Cite
|
Sign up to set email alerts
|

Altered Calcium Handling and Ventricular Arrhythmias in Acute Ischemia

Abstract: Acute ischemia results in deadly cardiac arrhythmias that are a major contributor to sudden cardiac death (SCD). The electrophysiological changes involved have been extensively studied, yet the mechanisms of ventricular arrhythmias during acute ischemia remain unclear. What is known is that during acute ischemia both focal (ectopic excitation) and nonfocal (reentry) arrhythmias occur, due to an interaction of altered electrical, mechanical, and biochemical properties of the myocardium. There is particular inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 129 publications
0
24
0
Order By: Relevance
“…Severe metabolic changes begin a few seconds after coronary occlusion: high-energy phosphates are hydrolyzed, intracellular pH lowers as a consequence of the activation of anaerobic glycolysis, and extracellular potassium levels increase [90,91] . The latter lasts for roughly 10 min, during which the resting membrane potential decreases, approaching the firing threshold potential, thus accelerating electrical conduction [92] . The intracellular acidosis also drives an increase in cytosolic calcium, facilitating early and late depolarization, as well as spatial and temporal fluctuations in the duration of action potentials [93] .…”
Section: Arrhythmogenic Metabolic Changes During Myocardial Ischemiamentioning
confidence: 99%
“…Severe metabolic changes begin a few seconds after coronary occlusion: high-energy phosphates are hydrolyzed, intracellular pH lowers as a consequence of the activation of anaerobic glycolysis, and extracellular potassium levels increase [90,91] . The latter lasts for roughly 10 min, during which the resting membrane potential decreases, approaching the firing threshold potential, thus accelerating electrical conduction [92] . The intracellular acidosis also drives an increase in cytosolic calcium, facilitating early and late depolarization, as well as spatial and temporal fluctuations in the duration of action potentials [93] .…”
Section: Arrhythmogenic Metabolic Changes During Myocardial Ischemiamentioning
confidence: 99%
“…In a recent study, Damasceno et al provided evidence to show that audiogenic epileptic seizure increased the peak amplitude of myocyte intracellular Ca ++ due to enhanced sympathetic activity (10). Myocardial Ca ++ overload contributes to myocardial tissue injury in various cellular mechanisms and may cause the generation of ventricular arrhythmias through the mechanism of delayed afterdepolarization (36)(37)(38). In the present study, the increased beta-adrenergic activation due to the possible excess adrenergic discharge may have caused myocardial cell Ca ++ overload.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, acute ischemia causes an increase in the frequency of Ca 2+ sparks that contributes to an increase in [Ca 2+ ] i (Mattiazzi et al, 2015a). The increase in [Ca 2+ ] i in ischemia is thought to be arrhythmogenic (Baumeister and Quinn, 2016) by driving excitatory after-depolarizations (Billman et al, 1991;Xing and Martins, 2004;Wu et al, 2011). Thus, if links exist between cell stretch and altered Ca 2+ handling in ischemia, they could represent important mechanisms for arrhythmogenesis.…”
Section: Mechanisms Of Ventricular Arrhythmias In Acute Regional Ischmentioning
confidence: 99%
“…Myocardial ischemia is also associated with an increase in [Ca 2+ ] i (Baumeister and Quinn, 2016), leading to a rise in Ca 2+ -calmodulin-dependent protein kinase II (CaMKII) activity (Mattiazzi et al, 2015b), which increases phosphorylation of RyR and the frequency of Ca 2+ sparks (Maier and Bers, 2007). Computational modeling has suggested that an elevation in [Ca 2+ ] i associated with hyperkalemia-induced membrane depolarization, along with a consequential reduction in NCXmediated Ca 2+ efflux and an increase in SR Ca 2+ content may also contribute to an increase in Ca 2+ spark rate in ischemia (Sato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%